2021
DOI: 10.1088/1742-6596/1717/1/012046
|View full text |Cite
|
Sign up to set email alerts
|

Cercospora Identification in Spinach Leaves Through Resnet-50 Based Image Processing

Abstract: Cercospora is a contagious disease that occurs in plant leaves. Spinach is one of the healthiest food that are preferred by the people nowadays. Thus cercospora is the disease that also occurs in the spinach leaves, it also affects the humans. It causes the serious effect in both the spinach plants and also human and animals consuming it. Therefore the usage of image processing and deep learning is done in order to find out the cercospora affected plant and preventing it from the spreading from one plant to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…The pooling procedure is executed by selecting as many elements as possible from the region of filter-covered layer depths. Each layer output in the residual block is passed on to the next layer and hops take place across the identity connections [51].…”
Section: Architecture Of Resnet50mentioning
confidence: 99%
“…The pooling procedure is executed by selecting as many elements as possible from the region of filter-covered layer depths. Each layer output in the residual block is passed on to the next layer and hops take place across the identity connections [51].…”
Section: Architecture Of Resnet50mentioning
confidence: 99%
“…Domain-general datasets here represent datasets that can be used for the training of CNNs for image classification or object detection, which then could be utilised for a particular application domain. For instance, ResNet-50 [17] has been trained on a domain-general dataset, ImageNet [31], and deployed for image classification tasks in various domains, such as medical [32], agriculture [33], autonomous driving [34], and so on. Contrary to domaingeneral, domain-specific datasets are originally created for a particular domain with the aim to facilitate learning of specialised domain-related features.…”
Section: ) Datasetsmentioning
confidence: 99%
“…Resnet is a residual network structure stacked by the residual blocks, which has performed well in image classication applications [21,22]. Literature [23] researched the advantage of Resnet-18 by comparing Resnet-18/50, VGG-19, and Googlenet and found that Resnet-18 has the advantages of short training time and high accuracy, developed a deep learning model base on ResNet-18 to diagnose the fan blade surface damage, and got good recognition e ect.…”
Section: Residual Networkmentioning
confidence: 99%